2019
DOI: 10.1038/s41416-019-0575-6
|View full text |Cite
|
Sign up to set email alerts
|

Negative plasma Epstein-Barr virus DNA nasopharyngeal carcinoma in an endemic region and its influence on liquid biopsy screening programmes

Abstract: Background Epstein-Barr virus (EBV)-associated nasopharyngeal carcinoma (NPC) in endemic regions may have undetectable plasma EBV DNA. Methods We prospectively recruited 518 patients with non-metastatic NPC and measured their pre-treatment plasma EBV DNA. The stage distribution and prognosis between pre-treatment plasma EBV DNA-negative (0–20 copies/ml) and EBV DNA-positive (>20 copies/ml) patients following radical treatment were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 45 publications
1
15
1
1
Order By: Relevance
“…The results showed that patients with plasma EBV DNA ≥1000 copies/mL, EA‐IgA ≥1:10 (and/or) VCA‐IgA ≥1:40 had significantly shorter periods of OS in comparison with other corresponding groups. Of note, the positive rate (71.6%) of plasma EBV DNA in present cohort was relatively low compared to previous studies (88%‐97%) 41,42 . Plasma EBV DNA levels were measured by quantitative PCR.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…The results showed that patients with plasma EBV DNA ≥1000 copies/mL, EA‐IgA ≥1:10 (and/or) VCA‐IgA ≥1:40 had significantly shorter periods of OS in comparison with other corresponding groups. Of note, the positive rate (71.6%) of plasma EBV DNA in present cohort was relatively low compared to previous studies (88%‐97%) 41,42 . Plasma EBV DNA levels were measured by quantitative PCR.…”
Section: Discussioncontrasting
confidence: 63%
“…Of note, the positive rate (71.6%) of plasma EBV DNA in present cohort was relatively low compared to previous studies (88%-97%). 41,42 Plasma EBV DNA levels were measured by quantitative PCR. The test results will be affected by the methods of DNA extraction, as well as the experiment instruments used in different labs.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, T1 cases were excluded because these cases had segmentation and assessment issues. However, a greater number of patients who were tested EBV DNA-negative had early-stage disease compared with patients who were tested EBV DNA-positive ( 15 ). We also found that tumor volume was another reliable choice for the radiologic evaluations of tumor burden because patients with positive pretreatment of EBV DNA plasma had larger tumor sizes.…”
Section: Discussionmentioning
confidence: 99%
“…In endemic regions, 17.2–29.3% of all newly diagnosed NPC patients have undetectable circulating EBV. 41 , 42 Second, large interlaboratory variability in the detection of circulating EBV DNA is also a factor, even when using the same PCR assay and identical procedures without harmonization. 43 Third, although pre-treatment plasma EBV DNA levels reflect the tumor burden and correlate with prognosis, the kinetics of circulating EBV DNA during chemoradiotherapy might add more prognostic value and identify distinct prognostic subtypes.…”
Section: Discussionmentioning
confidence: 99%